International Perspectives on Teachers Living with Curriculum Change (International Perspectives on English Language Teaching, 2018)
This book gives a voice to English language teachers faced with the challenges posed by English language curriculum change. As a core component of national state system curricula in virtually every country in the world, there has nevertheless been little research exploring how the millions of English teachers worldwide navigate the challenges posed by such curriculum changes. This volume includes eleven stories from teachers based across every continent, providing a global glimpse of how national English curriculum change projects have been experienced by classroom teachers who are commonly (if erroneously) viewed as mostly responsible for its implementation success or failure. The final chapter synthesises these experiences and suggests wider implications for the development of curriculum change planning processes, and how they might better support teachers' attempts to achieve curriculum goals. Edited and authored by leading experts in the field, this ground-breaking collection will be of interest to students and scholars of English language teaching, teacher education, curriculum change and education policy. Martin Wedell has recently retired as Head of International Education at the School of Education at the University of Leeds, UK. With more than 30 years' experience as a teacher and teacher educator, he has worked and lived around the world. His research focuses on better understanding the processes involved in planning and supporting English language curriculum changes. Laura Grassick is Teaching Fellow in TESOL at the University of Leeds, UK. Having taught in such diverse countries as South Korea, Bangladesh, Poland and the UK, her research interests lie primarily in English language curriculum change.